Leo Africanus discovers comedy theatre and poetry across the Mediterranean - Davis, Natalie Zemon 1928-2023 (Centre for Renaissance and Reformation Studies, 2021)
"Using the North African diplomat Hasan al-Wazzan, known in Europe as Leo Africanus (c. 1488-after 1532), as its guide, this book offers a comparative journey through the worlds of Arabic and Italian theatre and poetics in the late medieval and early modern period (1300-1600). Special attention to theatrical performances in Rome and in Italy in general, as well as in Tunis, Cairo, and in North Africa in general."--
Keywords: Aristoteles -- v384-v322 -- De arte poetica; Leo -- Africanus -- 1490-1550; Averroes -- 1126-1198; Cosmographia & geographia de Affrica; Geschichte -1600; Humanismus; Wissensvermittlung; Kulturleben; Drama; Theater -- Motiv; Islamische Literatur; Rezeption; Islam; Antike; Theater; Biografie; Italien; Leo / Africanus / approximately 1492-approximately 1550; Africanists / Europe / Biography; Theater / Africa, North / History; Theater / Italy / History; Arabic poetry / History and criticism; Italian poetry / History and criticism; Aristotle / Poetics; Europe / Intellectual life; Arab countries / Intellectual life; Poetics (Aristotle); Africanists; Arabic poetry; Intellectual life; Italian poetry; Arab countries; Europe; Italy; North Africa; Biographies; Criticism, interpretation, etc; History